2022
DOI: 10.1007/s40145-022-0588-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pellet surface roughness and pre-oxidation temperature on CMAS corrosion behavior of Ti2AlC

Abstract: Calcium-magnesium-alumina-silicate (CMAS) corrosion is a serious threat to thermal barrier coatings (TBCs). Ti2AlC has been proven to be a potential protection layer material for TBCs to resist CMAS corrosion. In this study, the effects of the pellet surface roughness and temperature on the microstructure of the pre-oxidation layer and CMAS corrosion behavior of Ti2AlC were investigated. The results revealed that pre-oxidation produced inner Al2O3 layer and outer TiO2 clusters on the pellet surfaces. The conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Based on the investigation on the interaction behavior of CMAS and CeO2, it could Based on the investigation on the interaction behavior of CMAS and CeO 2 , it could be found that CeO 2 is a useful material for mitigating CMAS attack to TBCs. Due to the excellent nucleating agent effect of the CeO 2 solid solution, one could design a T/EBC composition doped with Ce aiming to promote CMAS crystallization and suppress the melt penetration [49]. Meanwhile, based on the theory of optical basicity (OB), CeO 2 has a relatively moderate optical basicity (Λ = 1.01) compared to traditional TBC materials, which ensures that CeO 2 reacts with molten CMAS to form CeO 2 solid solution particles, promoting CMAS self-crystallization.…”
Section: Interface Interaction Between Molten Cmas and Ceo2 Pelletsmentioning
confidence: 99%
“…Based on the investigation on the interaction behavior of CMAS and CeO2, it could Based on the investigation on the interaction behavior of CMAS and CeO 2 , it could be found that CeO 2 is a useful material for mitigating CMAS attack to TBCs. Due to the excellent nucleating agent effect of the CeO 2 solid solution, one could design a T/EBC composition doped with Ce aiming to promote CMAS crystallization and suppress the melt penetration [49]. Meanwhile, based on the theory of optical basicity (OB), CeO 2 has a relatively moderate optical basicity (Λ = 1.01) compared to traditional TBC materials, which ensures that CeO 2 reacts with molten CMAS to form CeO 2 solid solution particles, promoting CMAS self-crystallization.…”
Section: Interface Interaction Between Molten Cmas and Ceo2 Pelletsmentioning
confidence: 99%
“…The Ti 2 AlC coatings are completely consumed after the CMAS corrosion for 6 h while the Ti 2 AlC pellets could resist the CMAS corrosion at the same temperature for 8 h without being destroyed [32]. When the Ti 2 AlC pellets contact with molten CMAS, a continuous inner Al 2 O 3 layer and a discontinuous outer TiO 2 layer can be formed on the surface [31,47]. According to the CaO-Al 2 O 3 -SiO 2 ternary phase diagram where the MgO content is 9 mol% from a study by Poerschke et al [48], as the Al 2 O 3 layer grows and dissolves into CMAS, the CMAS melt components adjacent to the Al 2 O 3 layer move from the liquid zone to the anorthite zone due to the Al enrichment, and TiO 2 exists as a solute in the CMAS melt with diffusion.…”
Section: Protectiveness Degradation Mechanism Of Ti 2 Alc Protective ...mentioning
confidence: 99%
“…The defects generated during this process can provide a pathway for oxygen diffusion and cause oxidation damage to the carbon matrix 19,20 . Our previous work 21,22 has proved that low‐loss film‐forming treatment (LFT) based on reduced film‐forming temperatures can significantly reduce oxidation losses 23–26 . The glass layer formed in situ by LFT at low temperatures has stable structure and inhibits cracking between phases in the coating 27 .…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Our previous work 21,22 has proved that low-loss film-forming treatment (LFT) based on reduced film-forming temperatures can significantly reduce oxidation losses. [23][24][25][26] The glass layer formed in situ by LFT at low temperatures has stable structure and inhibits cracking between phases in the coating. 27 Moreover, LFT can be accomplished in air environment without high temperature atmosphere and the cost is lower.…”
Section: Introductionmentioning
confidence: 99%